Bahasa Matematis Masyarakat Yogyakarta: Suatu Kajian Etnografi - Rully Charitas Indra Prahmana (Universitas Hamzanwadi, 2020)
Yogyakarta has a nickname as the City of Culture. Yogyakarta has several cultures that are closely related to the context of learning mathematics. However, not many educators in Yogyakarta see this culture as a context that can be a starting point in learning mathematics. Thus, this study aims to explore the culture of Yogyakarta's people that can be used as a context in learning mathematics. This study uses ethnographic studies sourced from literature studies, field observations, and interviews with informants who understand the ancient Javanese language well to clarify and / or provide more understanding of the results of the literature review collected. The results showed some mathematical languages used by the Yogyakarta people in Javanese that could be used as starting points in learning mathematics. This mathematical language includes the mention of numbers, area, angle, volume, indefinite units, and determination of time units.